Development and national scale implementation of an open-source electronic laboratory information system (OpenELIS) in Côte d'Ivoire: Sustainability lessons from the first 13 years. (February 2023) - He, Yao; Iiams-Hauser, Casey; Henri Assoa, Paul; Kouabenan, Yves-Rolland; Komena, Pascal; Pongathie, Adama; Kouakou, Alain; Kirk, Mary; Antilla, Jennifer; Rogosin, Carli; Sadate Ngatchou, Patricia; Kohemun, Natacha; et al.
Highlights: Factors for scaling and sustaining an eLIS in LMICs have not been previously described in the literature. Successful adoption, scaling, and sustainment of OpenELIS in Côte d'Ivoire relied on early collaboration with partners, regulatory agencies, and technical experts into every step of the design, implementation, and evaluation phases. Entities planning to nationally scale an eLIS should plan for 1) workforce development in both end users and system administrators; 2) financial sustainability; and 3) institutionalization of government ownership and technical leadership. An open-source eLIS can increase accuracy and timeliness of clinical laboratory data supporting diagnostic testing and monitoring in a resource limited setting such as Cote d'Ivoire. Abstract: Purpose: Côte d'Ivoire has a tiered public health laboratory system of 9 reference laboratories, 77 laboratories at regional and general hospitals, and 100 laboratories among 1, 486 district health centers. Prior to 2009, nearly all of these laboratories used paper registers and reports to collect and report laboratory data to clinicians and national disease monitoring programs. Project: Since 2009 the Ministry of Health (MOH) in Côte d'Ivoire has sought to implement a comprehensive set of activities aimed at strengthening the laboratory system. One of these activities is the sustainable development, expansion, and technical support of an open-source electronic laboratory information system (OpenELIS), with the long-term goal of Ivorian technical support and managerial sustainment of the system. This project has addressed the need for a comprehensive, customizable, low- to no-cost, open-source LIS to serve the public health systems with initial attention to HIV clients and later expansion to cover the general population. This descriptive case study presents the first published summary of original work which has been ongoing since 2009 in Côte d'Ivoire to transform the laboratory information management systems and processes nationally. Impact: OpenELIS is now in use at 106 laboratories across Côte d'Ivoire. This article describes the iterative planning, design, and implementation process of OpenELIS in Côte d'Ivoire, and the evolving leadership, ownership, and capacity of the Ivorian MOH in sustaining the system. This original work synthesizes lessons learned from this 13-year experience towards strengthening laboratory information systems in other low resource settings.